Pengaruh Pembelajaran Kitab Hadiyyah Al-‘Arus terhadap Kesiapan Menikah Santri Pondok Pesantren An-Nur 1 Asrama Az Zubaidah Malang (Pusat Riset dan Inovasi Nasional, 2026)
This study examines the influence of teaching the classical text Hadiyyah al-‘Arus on the mindset of female students (santri putri) regarding their readiness for marriage: A case study at Pondok Pesantren Putri An Nur 1 (Asrama Az-Zubaidah), Malang. The research departs from the recognition that pre-marital education in Islamic boarding schools (pesantren) should extend beyond mere Islamic legal aspects and actively shape the students’ mindset as well as their mental, emotional, and spiritual preparedness to embrace marriage as an act of worship (ibadah) and a sacred trust (amanah). The study employed a qualitative approach with field research design. Data were collected through participant observation, in-depth interviews, documentation, and relevant literature review. The data were subsequently analyzed using descriptive-analytical methods to identify the relationship between the teaching of Hadiyyah al-‘Arus and the students’ marital readiness. The findings reveal that the systematic study of Hadiyyah al-‘Arus significantly shapes the students’ mindset. The santri no longer view marriage merely as a physical or social union but as a profound spiritual trust that demands religious, emotional, and moral preparedness. They emphasize the importance of selecting a spouse based primarily on religious commitment and good character (din and akhlaq), understanding the rights and obligations of husband and wife, and avoiding excessive or extravagant wedding celebrations (walimah). It can be concluded that Hadiyyah al-‘Arus serves as a highly effective medium for pre-marital education in the pesantren context, successfully fostering comprehensive understanding, positive attitudes, and awareness among female students toward building a tranquil, loving, and merciful family (sakinah mawaddah wa raḥmah). The study recommends the continued and systematic integration of classical turath texts into pesantren curricula as well as further research with broader and comparative scope.